STUDI KONDISI DAN METODE PEMELIHARAAN JALAN NASIONAL DI PROVINSI SULAWESI TENGAH (STUDI KASUS : RUAS KEBONSARI (PALU) – JALAN TANAH RUNTUH, KEBONSARI (TALISE) – TAWAELI DAN TOLAI - SAUSU) - Rahman, Muhammad Awalur (Jurnal Sains dan Teknologi Tadulako, 2024)
Road infrastructure that is burdened by high and repetitive traffic volumes will cause a decrease in road quality which can be seen from the condition of the road surface, both structurally and functionally damaged, so it is necessary to study the condition and find ways to maintain it using the IRMS program. . The method used in this research is the Integrated Road Management System (IRMS) Program. The required input data are road surface roughness data (IRI), traffic data, road condition data, road inventory data, and reference point data. Based on the results of the IRI predictive condition analysis, the application output for Kebonsari (Talise) – Tawaeli Road, Tanah Runtuh - Kebonsari (Palu) Road, and Tolai - Sausu Road Section is good and moderate for 5 years of analysis. The recommended maintenance treatment for 5 years of analysis for each segment is; 1) Kebonsari (Talise) – Tawaeli road includes routine maintenance, and routine maintenance of conditions; 2) The Tanah Runtuh - Kebonsari (Palu) road section includes routine maintenance, and routine maintenance of conditions; and 3) Tolai - Sausu Road Section includes routine maintenance and condition routine maintenance. The total cost is in including with the recommendations for maintenance from 2021 to 2025 for the Kebonsari (Talise) - Tawaeli Road Section of IDR 3,100,000,000 -, for the Tanah Runtuh - Kebonsari (Palu) Road Section of IDR 2,886,000,000 and Tolai - Sausu Road Section of Rp.12,333,000,000.-.